Articulatio Genu Examination Technique With Suspected Osteoarthritis At North Sumatera University Hospital - Ardianta, Jonas (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
The articulatio genu is a complex hinge joint and is formed by the distal part of the femur bone, condyle, epicondyle, proximal part of the tibia bone. Osteoarthritis is a degenerative joint disease that appears to be related to the aging process, obesity or joint trauma. The projection used in the Articulatio Genu examination with suspected Osteoarthritis at the North Sumatra Hospital Medan Installation uses the AP Weigh Bearing projection and lateral projectionThe results of this research are examination of the genu with suspected osteoarthritis using the AP Weigh Bearing projection.